1987
DOI: 10.1093/carcin/8.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by indomethacin and 5,8,11,14-eicosatetraynoic acid of the induction of rat hepatic ornithine decarboxylase by the tumor promoters phenobarbital and 12-O-tetradecanoylphorbol-13-acetate in vivo

Abstract: The involvement of arachidonate metabolism in the induction of rat hepatic ornithine decarboxylase (ODC) activity by the tumor promoters 12-O-tetradecanoylphorbol-13-acetate (TPA) and phenobarbital (PB) was investigated. Pretreatment of the rats with indomethacin or 5,8,11,14-eicosatetraynoic acid dose dependently inhibited the induction of ODC by both tumor promoters. Both inhibitors were more potent inhibitors of PB induction than TPA induction of ODC. The data are consistent with an involvement of arachidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results in Figure 7 suggest that the cyclooxygenase and PLA 2 inhibitors, indomethacin and BPB, have little effect on enhancement of hepatocyte DNA synthesis by PB and similar results were obtained with other liver promoters tested. Thus, despite evidence that such inhibitors impair the effects of PB as a promoter (Denda et al, 1994) and as an ornithine decarboxylase inducer (Van Rooijen et al, 1987) in vivo, the study suggests that direct promoter action on hepatocytes to stimulate DNA synthesis is not blocked by these inhibitors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The results in Figure 7 suggest that the cyclooxygenase and PLA 2 inhibitors, indomethacin and BPB, have little effect on enhancement of hepatocyte DNA synthesis by PB and similar results were obtained with other liver promoters tested. Thus, despite evidence that such inhibitors impair the effects of PB as a promoter (Denda et al, 1994) and as an ornithine decarboxylase inducer (Van Rooijen et al, 1987) in vivo, the study suggests that direct promoter action on hepatocytes to stimulate DNA synthesis is not blocked by these inhibitors.…”
Section: Discussionmentioning
confidence: 60%
“…Further evidence to associate prostaglandins with the action of PB in rat liver comes from studies on ornithine decarboxylase regulation. Van Rooijen et al (1987) showed that the induction of ornithine decarboxylase by PB in vivo was blocked by indomethacin and by the cyclooxygenase/lipooxygenase inhibitor 5,8,11,14‐ eicosatetraynoic acid (ETYA). Using a different promoting regimen, Gupta et al (1989) found elevated levels of PGE 2 in the livers of rats fed a choline‐deficient diet and indomethacin was shown to suppress the induction of γ‐glutamyl transpeptidase‐positive foci in livers of initiated rats.…”
mentioning
confidence: 99%
“…The induction of glycogenolysis after administration of phorbol ester [1,2], endotoxin [3] or platelet-activating factor [4] to the perfused liver was found to be meditated by eicosanoids produced in the liver. Eicosanoids were also reported to be involved in the induction of the enzyme ornithine decarboxylase in the liver after administration of phorbol ester in vivo [5][6][7]. Since phorbol ester and endotoxin were not able to induce these metabolic effects in isolated parenchymal liver cells, a new concept for the regulation of liver metabolism was presented (1)(2)(3)(4)6,8).…”
Section: Introductionmentioning
confidence: 99%